1997
DOI: 10.1002/actp.1997.010480905
|View full text |Cite
|
Sign up to set email alerts
|

Effective conjugation length and UV/vis spectra of oligomers

Abstract: On the basis of an extended series of monodisperse oligomers of the dialkoxy-substituted phenyleneethenylenes la-i the Eqs.(3) and (4) were conceived in order to determine the limiting values of the energies Ei and the wavelengths di of the W / v i s absorption. The convergence of the Ei and l i values with a growing number n of repeating units pennits a precise prediction of the Ei,,,, and ,Ii,,,, values of the corresponding polymer 1 j as well as a statement about the overall effect of conjugation mi and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
432
2
25

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(492 citation statements)
references
References 36 publications
33
432
2
25
Order By: Relevance
“…We found that the best fit of the data as a function of chain length, n, is obtained when assuming an exponential dependence 1Þ with IP N , A and t being fitting parameters; IP N can be recognized as the polymer (infinite chain) ionization potential. A similar equation has been used before to describe the optical spectra (Meier et al 1997;Gierschner et al 2006). The HOMO energy was also used to estimate the ionization potential in the framework of Koopmans' (1933) theorem.…”
Section: (C ) Ionization Potentialsmentioning
confidence: 99%
“…We found that the best fit of the data as a function of chain length, n, is obtained when assuming an exponential dependence 1Þ with IP N , A and t being fitting parameters; IP N can be recognized as the polymer (infinite chain) ionization potential. A similar equation has been used before to describe the optical spectra (Meier et al 1997;Gierschner et al 2006). The HOMO energy was also used to estimate the ionization potential in the framework of Koopmans' (1933) theorem.…”
Section: (C ) Ionization Potentialsmentioning
confidence: 99%
“…The inhomogeneous broadening of the site energies was introduced via a Gaussian distribution of the transition energies of the spectroscopic units. The energy of a spectroscopic unit has also been correlated to its length using the energies given for MEH-PPV-like oligomers in chloroform reported by Meier et al 40 Figs. 3͑a͒ and 3͑b͒.…”
Section: ͑1͒mentioning
confidence: 99%
“…1u, 43 The parameters a and b, respectively, have to be optimized on the basis of the measured λ max (n). Normally, four data points are sufficient for an accurate prediction of λ ∞ .…”
Section: Methodsmentioning
confidence: 99%